Map Series No. 13 May, 1965 ? Hardness Of Water From The Upper Part Of The Floridan Aquifer In Florida - William J. Shampine (Society for Mining, Metallurgy & Exploration, 1966)
The Floridan aquifer, which underlies all of Florida, yields water with a hardness of less than 180 pmts per million (ppm) in the northwestern part and throughout much of the center of the Slate. In most of the rest of the Stale, the aquifer yields water having a hardness greater than 180 ppm and as much is 1,900 ppm. Hardness of ground water is caused by dissolved salts from the geologic formations through which the water passes or by direct pollution. Sometimes pollution may indirectly increase the hardness of ground water by increasing the acid content and thus increasing the solution of calcium and magnesium salts. Water from deep zones of the aquifer lend to he harder than water from more shallow zones. Only the hardness of water from the upper part of the aquifer is shown.